Plot and Composition: Temporal and Atemporal Relationships in Short German-Language Literary Narratives - V. A. Andreeva (Научный диалог, 2025)
This article attempts to reconceptualize traditional notions of poetics from the perspective of a cognitive-discursive paradigm. Plot and composition are examined as integral elements of narrative, relating them to its anthropocentric components — the narrator, the abstract author, and the abstract reader. The findings are based on an analysis of a corpus of German-language short prose, allowing for conclusions regarding the genre-specific characteristics of plot and composition in short stories. The narrative method of material interpretation reveals that plot and composition are grounded in temporal and atemporal relationships, respectively. It is emphasized that the plot reflects the causal determination of parts (episodes) of the narrative, while composition pertains to its functional-pragmatic aspects. This distinction positions the plot within the fictional level of the communicative structure of the narrative, whereas composition aligns with the abstract level. It is demonstrated that the lack of eventfulness in the plot of a short story obstructs access to the narrative’s eventfulness, which is regarded in narratology as a distinctive feature of narrative. Furthermore, it is established that the eventfulness of short narratives is shaped along the axis of composition, which contains pragmatic signals that coalesce into an interpretative framework reflecting the author’s perceptions of the reader’s interpretative possibilities. The author concludes that it is indeed composition, rather than the eventless plot of the short story, that provides the essential criterion for narrative, expressed through the narrative punch.